PENG ARUH VARIABEL MONETER DAN HARGA MIN YAK DOMESTIK TERHADAP INFLASI DI INDONESIA PERIODE 2009 2019 - Nur Shomita Hidayati; Maski, Ghozali (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Inflation is one of the references that can be used as a tool to measure or see the economic stability of a country. To maintain stability from inflation, it is necessary to implement monetary policy. This study intends to determine the effect of variables that can affect inflation in Indonesia in 2009-2019. The main variables used in this study are the money supply, interest rates, exchange rates and domestic oil prices due to the finding of gaps between factual data and theory in these variables. The method used is the Partial Adjustment Model (PAM). The results of this study indicate that the money supply, exchange rate, and domestic oil prices have no significant effect on inflation in Indonesia in 2009-2019. Meanwhile, interest rates have a positive and significant impact on inflation in Indonesia in 2009-2019.